2018
DOI: 10.3892/mmr.2018.9165
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of microRNA‑660 inhibits cell proliferation and invasion in osteosarcoma by directly targeting forkhead box O1

Abstract: The abnormal expression of microRNAs (miRNAs/miRs) has been observed in osteosarcoma (OS), and these differently expressed miRNAs contribute to the occurrence and development of OS by regulating various biological behaviours. Therefore, a comprehensive understanding of the detailed roles of aberrantly expressed miRNAs in OS progression may be favourable to the identification of promising therapeutic strategies for the treatment of patients with this malignancy. The present study demonstrated that miR‑660‑5p (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…MiR-215-5p and miR-642a-5p may be potential biomarkers for diagnosis of osteosarcoma [19]. And miR-660 promotes osteosarcoma cell proliferation and invasion [20].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-215-5p and miR-642a-5p may be potential biomarkers for diagnosis of osteosarcoma [19]. And miR-660 promotes osteosarcoma cell proliferation and invasion [20].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, studies have shown that the miRNA-34 family (miRNA-34a, miRNA-34b, and miRNA-34c) can also affect multiple target genes including the Notch signaling pathway, thereby affecting the pathogenesis of OS [12]. In addition, Zhang et al [13] studies have also shown that miRNA-34c can not only play a carcinogenic role by inhibiting the expression of the Notch signaling pathway, but also directly inhibit the normal differentiation of osteoblasts, leading to a cell cycle regulation disorder. Other reduced-expressing miRNAs, such as miRNA-218, were also reduced significantly in human OS tissues and OS cell lines (SAOS-2 cells), and transfection of miRNA-218 gives SAOS-2 cells the ability to invade and metabolize distantly.…”
Section: Mirna and Os Occurrence And Developmentmentioning
confidence: 99%
“…Micrornas (mirnas/mirs), are short, noncoding single-stranded rnas that regulate gene expression, and their roles as regulators of Bn pathogenesis has been reported (6,7). For example, one study found that mir-367-5p downregulation promoted the proliferation of osteoblasts in a model of microgravity-induced bone healing.…”
Section: Introductionmentioning
confidence: 99%